2012
DOI: 10.1371/journal.pone.0040523
|View full text |Cite
|
Sign up to set email alerts
|

GM-CSF Priming Drives Bone Marrow-Derived Macrophages to a Pro-Inflammatory Pattern and Downmodulates PGE2 in Response to TLR2 Ligands

Abstract: In response to pathogen recognition by Toll-like receptors (TLRs) on their cell surface, macrophages release lipid mediators and cytokines that are widely distributed throughout the body and play essential roles in host responses. Granulocyte macrophage colony-stimulating factor (GM-CSF) is important for the immune response during infections to improve the clearance of microorganisms. In this study, we examined the release of mediators in response to TLR2 ligands by bone marrow-derived macrophages (BMDMs) prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 65 publications
(69 reference statements)
3
29
0
Order By: Relevance
“…In this study, we showed that high potential of SKG T cells to produce GM-CSF produced a different outcome between zymosan-treated SKG and BALB/c. GM-CSF was reported to upregulate TLR2, TLR4, and CD14 expression (41)(42)(43) and boost IL-6 and IL-1b production from macrophages (41,44,45). Although serum concentration of GM-CSF in zymosan-treated SKG mice was very low and could not be detected by ELISA, we showed that GM-CSF could enhance the production of IL-6 and IL-1b by macrophages even at a low concentration (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…In this study, we showed that high potential of SKG T cells to produce GM-CSF produced a different outcome between zymosan-treated SKG and BALB/c. GM-CSF was reported to upregulate TLR2, TLR4, and CD14 expression (41)(42)(43) and boost IL-6 and IL-1b production from macrophages (41,44,45). Although serum concentration of GM-CSF in zymosan-treated SKG mice was very low and could not be detected by ELISA, we showed that GM-CSF could enhance the production of IL-6 and IL-1b by macrophages even at a low concentration (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…(3) Additionally, iM and iDC in the naïve situation have differentiated under influence of M-CSF, which makes them more responsive to T1-IFN signaling (94). During progression of Mtb infection, GM-CSF levels rise and increase the potential for IL-1β production by iM and iDC (94, 125, 155, 156). (4) Similar to the situation in gut infection, we propose that in tuberculosis (TB) IL-12 production in the lungs stimulates IFN-γ production by bone-marrow-resident NK cells, which locally primes monocytes (154).…”
Section: T1-ifns In Tbmentioning
confidence: 99%
“…(5) Additionally, IFN-γ stimulates monopoiesis over granulopoiesis by granulocyte/macrophage progenitor cells (128). (6) As Mtb infection progresses and GM-CSF levels increase, iM and iDC readily produce IL-1β [see also (3)] (124, 155), which can lead to PMN-mediated inflammatory damage in TB (120). (7) IL-1β production can be inhibited in response to either IFN-γ or IFN-β through mechanistically distinct pathways that differently affect Mtb killing.…”
Section: T1-ifns In Tbmentioning
confidence: 99%
“…In general it functions as a white blood cell growth factor. In addition, it has been shown to have roles in cell signaling [38] and in promoting inflammatory dendritic cells [39] and macrophages [40]. Furthermore, it has been implicated in the pathology of lung injury [41] and arthritic pain [42].…”
Section: Discussionmentioning
confidence: 99%